1990
DOI: 10.1021/es00081a002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of chlorination of aromatic compounds adsorbed on the surface of fly ash from municipal incinerators

Abstract: Aromatic substrates were adsorbed on the surface of fly ash from a municipal incinerator. Treatment with gaseous hydrogen chloride gave aromatic chlorination. Relative yields and isomer distributions indicate that an electrophilic mechanism is likely for the chlorination reaction. Inverse addition experiments were used to show that a surface-bound chlorinating agent is produced by the interaction of hydrogen chloride with the fly ash surface.Recycling experiments indicate that the fly ash surface functions as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 8 publications
0
41
1
Order By: Relevance
“…A higher copper concentration was found in the SeCu fly ash used in this study (260 mg/g) than has been found in MWI fly ash (0.3-4.6 mg/g) (Cains et al 1997). The zinc concentration in the fly ash used in this study was 166 mg/g, which was also higher than has been found in MWI fly ash (0.7-30.6 mg/g) (Hoffman et al 1990). The presence of chlorine is also an important factor that affects the formation of PCDD/Fs (Wikström et al 2003).…”
Section: Quality Control and Assurancecontrasting
confidence: 53%
“…A higher copper concentration was found in the SeCu fly ash used in this study (260 mg/g) than has been found in MWI fly ash (0.3-4.6 mg/g) (Cains et al 1997). The zinc concentration in the fly ash used in this study was 166 mg/g, which was also higher than has been found in MWI fly ash (0.7-30.6 mg/g) (Hoffman et al 1990). The presence of chlorine is also an important factor that affects the formation of PCDD/Fs (Wikström et al 2003).…”
Section: Quality Control and Assurancecontrasting
confidence: 53%
“…It has been found in a number of studies that the chlorine content affects POPs concentrations and that chlorination is an important POPs formation pathway [30,38]. The chlorination of naphthalene and less-chlorinated PCNs could be catalyzed by metal chlorides, such as CuCl 2 and FeCl 3 [29,30,38].…”
Section: Variations and The Factors Influencing Pcn Concentrations Inmentioning
confidence: 99%
“…We thought that dioxins were generated by a synergetic effect of proposed catalytic chlorination [18][19][20] by cupric and ferric chlorides, apart from for direct chlorination.…”
Section: Comparison Of Influences Among Heavy Metal Chloridesmentioning
confidence: 99%